Establishment of a vascular endothelial cell-reactive type II NKT cell clone from a rat model of autoimmune vasculitis. (19th September 2014) - Iinuma, Chihiro; Waki, Masashi; Kawakami, Ai; Yamaguchi, Madoka; Tomaru, Utano; Sasaki, Naomi; Masuda, Sakiko; Matsui, Yuki; Iwasaki, Sari; Baba, Tomohisa; Kasahara, Masanori; Yoshiki, Takashi; et al.
Abstract : An autoreactive type II NKT cell clone induces small-vessel vasculitis Abstract: We previously generated a rat model that spontaneously developed small vessel vasculitis (SVV). In this study, a T cell clone reactive with rat vascular endothelial cells (REC) was established and named VASC-1. Intravenous injection of VASC-1 induced SVV in normal recipients. VASC-1 was a TCRαβ/CD3-positive CD4/CD8 double-negative T cell clone with expression of NKG2D. The cytokine mRNA profile under unstimulated condition was positive for IL-4 and IFN-γ but negative for IL-2 and IL-10. After interaction with REC, the mRNA expression of IL-2, IL-5 and IL-6 was induced in VASC-1, which was inhibited by blocking of CD1d on the REC surface. Although the protein levels of these cytokines seemed to be lower than the detection limit in the culture medium, IFN-γ was detectable. The production of IFN-γ from the VASC-1 stimulated with LPS-pre-treated REC was inhibited by the CD1d blockade on the REC. These findings indicated VASC-1 as an NKT cell clone. The NKT cell pool includes two major subsets, namely types I and II. Type I NKT cells are characterized by expression of semi-invariant TCRs and the potential to bind to marine sponge-derived α-galactosylceramide (α-GalCer) loaded on CD1d; whereas, type II NKT cells do not manifest these characteristics. VASC-1 exhibited a usage of TCR other than the type I invariant TCR α chain and did not bind to α-GalCer-loaded CD1d; therefore, it was determined as a type II NKT cell clone. The collective evidence suggested that REC-reactive type II NKT cells could be involved in the pathogenesis of SVV in rats.